2019
DOI: 10.1080/14786419.2019.1616723
|View full text |Cite
|
Sign up to set email alerts
|

Three new steroidal saponins from the roots and rhizomes of Rohdea chinensis (Baker) N.Tanaka (synonym Tupistra chinensis Baker)

Abstract: Three new steroidal saponins from the roots and rhizomes of Rohdea chinensis (Baker) N.Tanaka (synonym Tupistra chinensis Baker)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The steroid saponins obtained from species of Liliaceae have shown the potential to significantly inhibit the proliferations of various human tumor cell lines in vitro [25][26][27][28][29]. Therefore, all isolated compounds were evaluated for their cytotoxicity against MHCC97H and H1299 by the MTT method.…”
Section: Resultsmentioning
confidence: 99%
“…The steroid saponins obtained from species of Liliaceae have shown the potential to significantly inhibit the proliferations of various human tumor cell lines in vitro [25][26][27][28][29]. Therefore, all isolated compounds were evaluated for their cytotoxicity against MHCC97H and H1299 by the MTT method.…”
Section: Resultsmentioning
confidence: 99%
“…T. chinensis, T. wattii, and T. yunnanensis are main sources of spirostanol and furostanol saponins. Sixty-five compounds were assigned as spirostanol saponins (Table 1 and Figure 2), 2,[7][8][9][10]21,22,24,28,[31][32][33]35,36,39 while compounds 85 to 150 are furostanol saponins (Table 1 and Figure 3). 5,8,10,18,22,24,31,35,37,[39][40][41][42][43][44][45][46][47] Taking spirostanol saponins into consideration, glycosylation generally happens at C-1, C-3, C-5, and C-24.…”
Section: Spirostanol and Furostanol Saponinsmentioning
confidence: 99%
“…Based on physicochemical results and NMR spectral analysis, Song et al reported that the 65% EtOH extract of T. chinensis underground parts contained 2 new spirostanol saponins, (24S,25R)-1β-hydroxy-3β-[(β-Dglucopyranoside)oxy]-spirost-5-en-24-yl-β-D-glucopyranoside (34), and (24S)-spirost-25 (27)-en-1β,3β,4β,5β,6β,24β-hexahydroxy-24-O-β-D-glucopyranoside (59), in addition to 2 known ones, 3-epi-diosgenin-3-β-D-glucopyranoside (32), and 25(R)-1β-hydroxy-spirost-5-en-3α-yl-O-β-D-glucopyranoside [3-epi-ruscogenin-3-β-D-glucopyranoside] (35). 8 In 2016, Xiang et al reported that the 60% EtOH extract of T. chinensis rhizome was characterized by the presence of 18 new compounds, (25R)-5β-spirostan-1β,3β-diol-3-O-β-D-fructofuranosyl-(2→6)-β-D-glucopyranoside (46), (25R)-5β-spirostan-1β, 3α-diol-3-O-β-D-glucopyranoside (47) 9,10,22,39 Thus, the root and rhizome of T. chinensis may be thought of as a rich resource of new spirostanol saponins. In another phytochemical report, apart from the known compound rhodeasapogenin 1-(β-D-xylopyranoside) (44), the 95% EtOH extract of Chinese T. chinensis rhizome also contained one new steroidal saponin, tupichinin A (72).…”
Section: Spirostanol and Furostanol Saponinsmentioning
confidence: 99%
See 2 more Smart Citations